Digital Concealment in Money Laundering: A technology-neutral approach to aggravated criminal liability in Indonesia - Shendy Prasetyo; Milda Istiqomah; Bambang Sugiri (IJBLE Scientific Publications Community Inc., 2026)
The increasing use of digital anonymity technologies has transformed the modus operandi of money laundering, creating new challenges for criminal law enforcement. Although a Virtual Private Network (VPN) is a legitimate cybersecurity technology, its deliberate misuse may conceal digital identities, obstruct financial investigations, and complicate asset tracing. This study examines the Indonesian legal framework governing money laundering involving VPNs and evaluates whether their intentional use should constitute an aggravating circumstance. This research employs normative legal research using statutory, conceptual, and comparative approaches. The findings reveal that Indonesian anti-money laundering legislation is capable of prosecuting offenses involving VPNs; however, it lacks normative differentiation regarding the intentional use of anonymity-enhancing technologies. This study argues that such misuse increases the offender's culpability and the social harmfulness of the offense, thereby justifying enhanced criminal sanctions. Accordingly, the study proposes a technology-neutral reform introducing the intentional misuse of VPNs and similar technologies as a statutory aggravating circumstance in Indonesia's anti-money laundering regime.